Patterns of oxytocin use for induction and augmentation of labour among healthcare providers in Nigeria - Chioma S. Ejekam; Ifeoma P. Okafor; Kehinde S. Okunade; Uchenna Igbokwe; Jude Nwokike (BMC, 2024)
Abstract Background The practice of intrapartum use of oxytocin for induction and augmentation of labour is increasing worldwide with documented wide variations in clinical use, especially dose administrations. There is also evidence of intrapartum use by unauthorized cadre of staff. Aim This study assessed the patterns - frequency of intrapartum use of oxytocin, the doses and routes of administration for induction and augmentation of labour, and identified the predictors of oxytocin use for induction and augmentation of labour by healthcare providers in Nigeria. Methods This was a cross-sectional study conducted among healthcare providers - doctors, nurses/midwives and community health workers (CHWs) in public and private healthcare facilities across the country's six geopolitical zones. A multistage sampling technique was used to select 6,299 eligible healthcare providers who use oxytocin for pregnant women during labour and delivery. A self-administered questionnaire was used to collect relevant data and analysed using STATA 17 statistical software. Summary and inferential statistics were done and further analyses using multivariable regression models were performed to ascertain independent predictor variables of correct patterns of intrapartum oxytocin usage. The p-value was set at < 0.05. Results Of the 6299 respondents who participated in the study, 1179 (18.7%), 3362 (53.4%), and 1758 (27.9%) were doctors, nurses/midwives and CHWs, respectively. Among the respondents, 4200 (66.7%) use oxytocin for augmentation of labour while 3314 (52.6%) use it for induction of labour. Of the 1758 CHWs, 37.8% and 49% use oxytocin for induction and augmentation of labour, respectively. About 10% of the respondents who use oxytocin for the induction or augmentation of labour incorrectly use the intramuscular route of administration and about 8% incorrectly use intravenous push. Being a doctor, and a healthcare provider from government health facilities were independent positive predictors of the administration of correct dose oxytocin for induction and augmentation of labour. The CHWs were most likely to use the wrong route and dose administration of oxytocin for the induction and augmentation of labour. Conclusion Our study unveiled a concerning clinical practice of intrapartum oxytocin use by healthcare providers in Nigeria - prevalence of intrapartum use of oxytocin, inappropriate routes of administration for induction and augmentation of labour, varied and inappropriately high start dose of administration including unauthorized and high intrapartum use of oxytocin among CHWs.